Rubber hand illusion induced by touching the face ipsilaterally to a deprived hand: evidence for plastic “somatotopic” remapping in tetraplegics - Scandola, Michele; Tidoni, Emmanuele; Avesani, Renato; Brunelli, Giovanni; Aglioti, Salvatore M.; Moro, Valentina (Frontiers in Human Neuroscience, 2014)
Background: Studies in animals and humans indicate that the interruption of body-brain connections following spinal cord injury (SCI) leads to plastic cerebral reorganization. Objective: To explore whether inducing the Rubber Hand Illusion (RHI) via synchronous multisensory visuo-tactile bodily stimulation may reveal any perceptual correlates of plastic remapping in SCI. Methods: In 16 paraplegic, 16 tetraplegic and 16 healthy participants we explored whether RHI may be induced by tactile stimuli involving not only the left hand but also the left hemi-face. Touching the participant’s actual hand or face was either synchronous or asynchronous with tactile stimuli seen on a rubber hand. We assessed two components of the illusion, namely perceived changes in the real hand in space (indexed by proprioceptive drift) and ownership of the rubber hand (indexed by subjective responses to an ad-hoc questionnaire). Results: Proprioceptive drift and ownership were found in the healthy group only in the condition where the left real and fake hand were touched simultaneously. In contrast, no drift was found in the SCI patients who, however, showed ownership after both synchronous and asynchronous hand stroking. Importantly, only tetraplegics showed the effect also after synchronous face stroking. Conclusions: RHI may reveal plastic phenomena in SCI. In hand representation-deprived tetraplegics, stimuli on the face (represented contiguously in the somatic and motor systems), drive the sense of hand ownership. This hand-face remapping phenomenon may be useful for restoring a sense of self in massively deprived individuals.